1999
DOI: 10.1149/1.1391555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Conductivity of Zirconia Electrolytes on the Polarization Behavior of Various Cathodes in Solid Fuel Cells

Abstract: The polarization behaviors of porous platinum and La(Sr)MnO 3 (LSM) cathodes coupled with zirconia electrolytes with various ionic conductivities ( ion ) were investigated. The exchange current density, j 0 , on Pt cathode was not influenced by the ion at 900 and 1000ЊC, whereas j 0 increased proportionally to ion at a lower temperature of 800ЊC. However, the j 0 on LSM cathodes increaesd in proportion to the ion in the temperature region between 800 and 1000ЊC. The dispersion of nanometer-sized Pt catalysts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 52 publications
4
23
1
Order By: Relevance
“…Furthermore, there can be several physicochemical reasons for investigating such correlations from the microscopic as well as macroscopic points of view: From the microscopic point of view, it should be remembered that the excellent correlations have been already obtained between the ionic conductivity of electrolyte and the electrode performance ; cathode/anode performance is enhanced with ionic conductivity of electrolyte. When this correlation is applied to degradation phenomena, the conductivity degradation may cause some cathode performance degradations.…”
Section: Correlation Between Cathode Overpotential and Ohmic Lossmentioning
confidence: 99%
“…Furthermore, there can be several physicochemical reasons for investigating such correlations from the microscopic as well as macroscopic points of view: From the microscopic point of view, it should be remembered that the excellent correlations have been already obtained between the ionic conductivity of electrolyte and the electrode performance ; cathode/anode performance is enhanced with ionic conductivity of electrolyte. When this correlation is applied to degradation phenomena, the conductivity degradation may cause some cathode performance degradations.…”
Section: Correlation Between Cathode Overpotential and Ohmic Lossmentioning
confidence: 99%
“…1,3 For example, the majority of noble metal infiltration-related research indicates that a small amount of infiltrated noble metal enhances electrochemical performance of baseline cathodes. [6][7][8][9][10][11] Conversely, a minority of researchers has reported that infiltrated Pd or Pt had little effect on cathode performance. 12,13 Conflicting results may be explicable once the underappreciated and essentially unexplored relationship of infiltrate/backbone structure is considered.…”
mentioning
confidence: 99%
“…Several reports cite conventional YSZ-LSM composite cathodes with precious metals or electrocatalytic perovskites used as promoters. [28][29][30] The cathode backbone adopted in the present study is the most common cathode for commercial SOFC, and contains a thin SDC-LSCF functional layer in contact with a YSZ electrolyte and a relatively thick LSCF current collecting layer. In the present study, the cathode functional layer directly participating in the electrode reaction has features of the type IV composite cathode.…”
mentioning
confidence: 99%